Fourier analysis of weekly soil moisture at Pune - SAMUI, R. P. (MAUSAM, 1994)
The wee!..l) soil moistu re data collected at Centra l Agromcl Observat ory ICA ~ M O J . Puuc Juril1~ 19 5 K·P~ S9 have been subjccctcd to Fo urie r analysis. With norm al dat a the amplit udc~ For Varillll'i dc pl h ~ '"U)' between 0 .76 In I . 1.2 em of wate r Iu r first harmonic and decrease sha rply \\ ith h igher order harmonic... l he •...rlucs for fourth harm onic range from 0 .0 3 to 0 ,07 em of water o nly. UUY, C\W, the highest amplit ude for the calendar vcars 19t'4. 19S5. IIJH7 and 19S9 i'i fou nd 10 va ry between 0 . 45 10 1. .15 ern of wat er irrespective Ill' -oi l dep ths. Under normal co ndit io n.. the ma ximu m so il moistu re nca r the soi l surface 0 .5 em dep th ! occurs on 15 September while at 30 em depth. the soil moi st ure ma vim um occurs on 2-4 September. a dcluy of 9 da) s. 1:, lf th e four soil dep ths co nsidered in thi s study. the first . second and third har mo nics rc pr c-sent rc..pc...Iivc 1,\ ~.46. 2-32 .\ 4-26 & 67-S6. 6-t 4 a r-d 1 · 6 ~,~ of total var iance res pecti ve ly for eac h of th e years 19S-4. 19S5. IIJg7 a nd t9~9 and normal dura. The cha nge in 'oil mUI..ture pattern after J une and October due In occ urrence (If southwe...t and northeast monsoon i~ wctl ref lected .